Anti-interleukin-8 activity of tick salivary gland extracts. - Hajnická, V; Kocáková, P; Sláviková, M; Slovák, M; Gasperík, J; Fuchsberger, N; Nuttall, P (2001)
Interleukin-8 (IL-8) is one of many mammalian chemokines (chemotactic cytokines) that direct mammalian inflammatory and immune cells to sites of injury and infection. Chemokines are produced locally and act on leucocytes through selective receptors. The principal role of IL-8 is to control the movement and activity of neutrophils. To date, several tick species have been shown to modulate the production or activity of certain cytokines but none of these are chemokines. Using an IL-8 specific ELISA, we showed that salivary gland extracts (SGE) from several ixodid tick species (Dermacentor reticulatus, Amblyomma variegatum, Rhipicephalus appendiculatus, Haemaphysalis inermis and Ixodes ricinus) reduced the level of detectable IL-8. Analyses of fractionated SGE revealed one similar peak of activity for D. reticulatus, A. variegatum and R. appendiculatus; a second peak, observed for D. reticulatus and A. variegatum, differed between the two species. Using radiolabelled IL-8, SGE and peak activity fractions of D. reticulatus were shown to bind the chemokine, and to inhibit binding of IL-8 to its receptors on human granuolocytes enriched for neutrophils. The biological significance of these observations was demonstrated by the ability of SGE to inhibit IL-8 induced chemotaxis of human blood granulocytes. Future isolation and characterization of the active molecules will enable determination of their functional roles in bloodfeeding and effect on tick-borne pathogen transmission.